The Impact of the Global Food Crisis on Self-Assessed Food Security - Headey, Derek D. (Oxford University Press on behalf of the World Bank, 2014)
We provide the first large-scale survey-based evidence on the impact of the global food crisis of 2007–08 using an indicator of self-assessed food security from the Gallup World Poll. For the sampled countries as a whole, this subjective indicator of food security remained the same or even improved, seemingly owing to a combination of strong economic growth and limited food inflation in some of the most populous countries, particularly India. However, these favorable global trends mask divergent trends at the national and regional levels, with a number of countries reporting substantial deterioration in food security. The impacts of the global crisis therefore appear to be highly context specific.